Cossidae (Lepidoptera) of the Russian Caucasus with the description of a new species - Yakovlev, Roman V.; Poltavsky, Alexander N.; Ilyina, Elena V.; Shchurov, Valeriy I.; Witt, Thomas J. (Zootaxa, 2015)
An annotated list of the Cossidae of the Russian portion of the Caucasus including 20 species from 11 genera and two subfamilies is presented for the first time. A new species Cryptoholcocerus daghestanica sp. nov. is also described.